2021
DOI: 10.1038/s41598-021-02643-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating PIK3CA mutation detection at diagnosis in non-metastatic inflammatory breast cancer patients

Abstract: Inflammatory breast cancer (IBC) is an aggressive BC subtype with poor outcomes. A targetable somatic PIK3CA mutation is reported in 30% of IBC, allowing for treatment by PI3Kα-specific inhibitors, such as alpelisib. The aim of this study was to evaluate the detection rate of circulating PIK3CA mutation in locally-advanced IBC (LAIBC) patients harbouring a PIK3CA mutation on initial biopsy. This monocentric retrospective study was based on available stored plasma samples and tumour biopsies at diagnosis from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
(49 reference statements)
1
4
0
Order By: Relevance
“…A study reported by Arteaga's group characterized the molecular profiling of the residual disease of patients with TNBC [43]. The investigators showed an enrichment of basal-like TNBC samples with MCL1 amplifications, PTEN deletions-mutations and JAK2 amplifications; enrichments occurred in genes constituting cell-cycle regulators and PI3K/ mTOR pathway, confirmed consistently in other studies [44][45][46][47]. Potential actionability of the genomic alterations was suggested, to select postneoadjuvant treatments.…”
Section: Molecular and Immunological Characteristic Of The Residual D...supporting
confidence: 54%
“…A study reported by Arteaga's group characterized the molecular profiling of the residual disease of patients with TNBC [43]. The investigators showed an enrichment of basal-like TNBC samples with MCL1 amplifications, PTEN deletions-mutations and JAK2 amplifications; enrichments occurred in genes constituting cell-cycle regulators and PI3K/ mTOR pathway, confirmed consistently in other studies [44][45][46][47]. Potential actionability of the genomic alterations was suggested, to select postneoadjuvant treatments.…”
Section: Molecular and Immunological Characteristic Of The Residual D...supporting
confidence: 54%
“…A high expression of PI3K is correlated with a larger tumor size, lymph node metastases, advanced tumor stage in TNBC [ 37 ], and unfavorable outcomes in various solid tumors [ 38 , 39 , 40 , 41 ]. The PI3K/mTOR pathway is also strongly activated in IBC tumors [ 42 ], and the PI3K/Akt and PI3K/mTOR pathways are crucial for IBC invasion [ 43 , 44 ]. In addition, PIK3CA is the second most commonly mutated gene after TP53 in both TNBC (16%) and IBC (29.5%) [ 11 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma-derived DNA is the most popular source of cell free DNA (cfDNA) for tumor follow-up and even for cancer diagnosis (Allouchery et al, 2021). One of its advantages is its simple collection.…”
Section: Discussionmentioning
confidence: 99%